(A study on physico-chemical properties of sago flour from various regions in indonesia). - Tumbel, Nicolas (Balai Besar Industri Agro, 1991)
Astudy on physico-chemical properties of sago flour has been done.The sago flour was obtained from various regions of indonesia i.e. Palembang,Banjar Baru,Ambon,Bogor,Sukabumi,Manado,and Irian Jaya.The analysis conducted were moisture,ash,protein,crude fat,crude fiber,starch,amylose & amylopectine,pH,amylograph,fungi test and particle size.The flour from Sukabumi was found out to be the best one.The improvement on sago flour production is still need to be done to get a better quality of flour.